ANALISIS MINAT BELAJAR SISWA SMA KELAS XI PADA MATERI MATRIKS - Nunung Hamidah; Wahyu Setiawan (Departement of Mathematics Education, 2019)
One of the affective aspects that play a role in mathematics learning is the interest in learning. The interest in learning plays a very important role and has a big impact on the attitudes and behavior of students. This study aims to determine the interest in learning class XI students. The method used in this study is descriptive-qualitative method. This research was conducted at MA Al-Barry. The population in this study was XI grade students at MA Al-Barry. The sample in this study was class XI A which amounted to 20 students. The instruments used were 5 test questions in the form of description questions and questionnaires or questionnaires consisting of 20 statements. Based on the results of data analysis and discussion seen from the percentage it can be concluded that mastery of matrix material and affective aspects of student learning interest is quite good even though there are some students whose interest in learning and understanding is still lacking.